Philosophical issues in the English School of international relations. (June 2023) - Bevir, Mark; Hall, Ian
This article responds to Charlotta Friedner Parrat's critique of our argument that the English School of international relations should embrace a more thoroughgoing interpretivism. We address four of Friedner Parrat's objections to our argument: that our distinction between structuralism and interpretivism is too stark; that our understanding of the relationship between agency and structure is problematic; that our approach would confine the English School to the study of intellectual history; and that the English School should eschew explanation. We argue that if the School is to use structuralism, it must be clearer about how it understands structures and their relationships to agents. We argue too that interpretivism not only offers a better account of situated agency, but also that it provides the English School with one way to move beyond the description and classification of institutions in international society towards better explanations of international relations.